2014
DOI: 10.1021/ar500063x
|View full text |Cite
|
Sign up to set email alerts
|

“Nano-oddities”: Unusual Nucleic Acid Assemblies for DNA-Based Nanostructures and Nanodevices

Abstract: CONSPECTUS: DNA is an attractive polymer building material for nanodevices and nanostructures due to its ability for self-recognition and self-assembly. Assembly relies on the formation of base-specific interactions that allow strands to adopt structures in a controllable fashion. Most DNA-based higher order structures such as DNA cages, 2D and 3D DNA crystals, or origamis are based on DNA double helices stabilized by Watson-Crick complementarity. A number of nonclassical pairing patterns are possible between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
128
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 79 publications
1
128
0
Order By: Relevance
“…These observations open an avenue for the identification of genomic C-rich sequences capable of forming stable i-motifs in vivo and provide essential information for the design and development of i-motif-based DNAn anodevices/biosensors for intracellular applications. [12] In biological terms,o ur results support the concept that i-motif structures may act as active regulators of genomic DNAa nd potential drug targets. [3,4,13] …”
supporting
confidence: 56%
“…These observations open an avenue for the identification of genomic C-rich sequences capable of forming stable i-motifs in vivo and provide essential information for the design and development of i-motif-based DNAn anodevices/biosensors for intracellular applications. [12] In biological terms,o ur results support the concept that i-motif structures may act as active regulators of genomic DNAa nd potential drug targets. [3,4,13] …”
supporting
confidence: 56%
“…Increasing evidence support biological roles for these oddities, [1,2] which may also find application in nanotechnologies [3] and biotechnologies (DNAzymes, aptamers…). [4,5] DNA quadruplexes are highly polymorphic: intramolecular structures may be parallel, antiparallel or "3+1" (three strands pointing in the same direction whereas the fourth one has the opposite polarity) although tetramolecular DNA quadruplexes tend to be all parallel.…”
Section: Introductionmentioning
confidence: 99%
“…[14] However, the construction of nanostructures based on non-canonical pairing is gaining importance and nanodevices based on motifs such as quadruplexes or triplexes have been described. [3] Both motifs (duplexes and quadruplexes) may be combined and the synapsis between duplexes and quadruplex structures have been shown at the molecular level [15,16] and have already been applied as a tool for the construction of nanomaterials [17,18] . In order to expand the applications of this hybrid duplexquadruplex structure, a deep understanding of their properties and folding process is required.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated their existence in human cells (15) and their involvement in cellular regulation including recombination (12), replication (13,14), transcription (10), and translation (11). On the other hand, synthetic G4s have been introduced as unique structural elements in nanotechnology (20) as well as aptamers for therapeutic and diagnostic purposes (21). For instance, the G-rich oligonucleotide AGRO100 (SI Appendix, Table S1), also known as AS1411, has been shown to exhibit potent antiproliferative activity against a range of cancer cells (21) and was later found to adopt multiple G4 conformations (22).…”
mentioning
confidence: 99%